The Role of TPACK in Strengthening Geometrical Thinking and Numeracy Literacy through Contextual Manipulative Media: A Qualitative Study Integrating Climate Literacy - Nadilah , Intan; Afifah, Ani; Supriyo, Supriyo; Darmawan, Puguh (Assyfa Journal of Multidisciplinary Education, 2025)
The need to improve the quality of education (SDG 4) urges the integration of global sustainability issues, such as climate literacy, into the core curriculum, particularly mathematics. This study stems from the urgency of improving students' geometric thinking and numeracy literacy, which remains a challenge, while emphasizing the importance of teachers' roles as learning designers. Objective: This study aims to explore in-depth the role of teachers' TPACK (Technological Pedagogical Content Knowledge) in planning, implementing, and reflecting on the use of contextual manipulative media that integrates climate literacy to strengthen students' conceptual understanding of geometry and numeracy. This study uses a qualitative approach with a case study design. Data were collected through in-depth classroom observations, semi-structured interviews with teachers and students, and analysis of learning documents (Lesson Implementation Plans and student artifacts) from teachers who implemented the TPACK framework. The findings indicate that the TPACK framework significantly guides teachers in selecting mathematically relevant climate content (PCK), designing effective and adaptive manipulative media (TCK/TPK), and facilitating critical discussions (PK) that link mathematical calculations (numeracy) to climate-based solutions. The role of TPACK enables a shift from passive learning to active and meaningful learning. Conclusion: The integration of climate literacy through contextual manipulative media, facilitated by strong TPACK mastery, not only successfully strengthens understanding of geometry and numeracy but also increases students' awareness and ability to apply mathematical knowledge to sustainability issues. These results provide important implications for teacher professional development in the digital and sustainability era.